Sistem Informasi Pemantauan Kinerja Guru Berbasis Web di SMA Katolik Santa Maria Hombakaripit - Stefani Intan Marukedu; Vinsensius Aprila Kore Dima; Katarina Yunita Riti (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2025)
The rapid development of information technology has provided great opportunities to improve the quality of educational management, particularly in terms of teacher performance evaluation and monitoring. At SMA Katolik Santa Maria Homba Karipit, the process of monitoring teacher performance is still conducted manually through written reports and administrative assessments, which often causes obstacles such as delays in data processing, information redundancy, and a lack of transparency in presenting evaluation results. This research aims to design and implement a web-based teacher performance monitoring information system that facilitates data collection, information processing, and report presentation more quickly, accurately, and in an integrated manner. The research applies the waterfall system development model, which includes the stages of requirements analysis, system design, implementation, testing, and evaluation. The web-based system was developed using PHP programming language and MySQL database, allowing it to be accessed flexibly through the internet. The results of the study indicate that the developed system successfully improves the efficiency of teacher performance data management, accelerates report generation, and provides real-time access for the school management, including principals and evaluation teams. Furthermore, the system also supports greater transparency and accountability, as all data are well-recorded and easily traceable. Therefore, the implementation of this web-based teacher performance monitoring system is expected to be an effective solution in supporting school management quality and promoting teacher professionalism at SMA Katolik Santa Maria Homba Karipit